Politics Or Demagogy? André Ventura’s populism in the presidential elections (Portugal, 2021) - Marcos Camilo, Eduardo José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Analysis on the speech of André Ventura (AV) in the television debates on the generalist Portuguese channels, RTP, SIC, TVI during the campaign for the presidential elections of January 2021. Study crossing semiotics and rhetoric. Semiotics will enable us to understand how AV discourse was inscribed in a political resentment. In turn, the rhetorical analysis will be useful to demonstrate the way in which his register moved away from a traditional paradigm of political expressiveness (inscribed in the deliberative genre) to one related to the judicial genre, in the scope of which it was generated a denouncement and stigmatization discursivity.